Irrigated vegetable production interventions in humanitarian emergencies: Ethiopia country deep dive - Singh, Radhika; Minh, Thai Thi; Schmitter, Petra S. (International Water Management Institute, 2024)
Ethiopia is grappling with escalating humanitarian crises, including conflict-induced displacement and climate-related emergencies, and therefore mounting humanitarian needs. However, amidst these challenges, there is hope in the form of irrigated vegetable production (IVP) interventions, which have the potential to significantly decrease household vulnerability and build resilience to future shocks and stresses. Most importantly, these interventions aim to empower households by helping them generate additional income and improve their nutrition.